BIOGAS FROM SOLID WASTE OF TOFU PRODUCTION AND COW MANURE MIXTURE: COMPOSITION EFFECT - Ni’mah, Lailan (CHEMICA: Jurnal Teknik Kimia, 2014)
The demand of conventional energy (fossil fuel) is increasing as the human population growth. The fuel from petroleum is the energy source from fossil fuel which is un-renewable, the price is also tend to me more expensive due to the absence of demand and supply balance. The fuel crisis indicate that the fossil fuel belong to Indonesia is decreasing. The limited of fosil fuel lead to the need to the development of renewable energy and energy conservation. One of the alternative energy is biogas which can be produced from solid waste of tofu production (SWTP). Tofu production waste has high acidity so that it needs a buffer in biogas production. One of the buffer which can be utilized is cow manure.The experiment was done in a batch anaerobic reactor. As many as 800 ml of sample was entered to the reactor with the capacity of 1 L, then incubated in an anaerobic condition in the room at the temperature of 25-30oC within 30 days. There are 8 variation apply in this research, they are KS:KT=100:0,75:25, 50:50,25:75 and 0:100 at VS of 3%, and KS:AT 50:50 at VS of 2%,4% and 5%. The measured parameter is the biogas volume, methane concentration, carbon dioxide concentration, the ratio of C vs N, total solid (TS) and volatile solid content (VS), volatile fatty acid (VFA), pH and temperature. The gas volume measurement was done every day using gasholder while methane concentration was measured by gas chromatography (GC).Research results shows that the composition of cow manure and SWTP at VS of 3% KS:AT = 50:50 shows the highest methane concentration. Optimal retention time to increase the production of biogas is start 14-28 days with the improvement methane concentration is 68,98% at 21st day.